Ramadan and strengthening of the social capital of Indonesian Muslim communities - Shalihin, Nurus (HTS teologiese studies, 2020)
This study aims to examine the relationship between Ramadan and social capital, that is, social solidarity and philanthropy, in Muslim communities in Indonesia. The data waere collected through a questionnaire that was distributed to 600 respondents in six districts or cities in two provinces. Respondents were randomly selected at the village level. The results showed that social solidarity during Ramadan was high (3.32) with values of the spirit of togetherness (3.37), collective consciousness (3.32) and cooperation (3.28). In addition, philanthropy was included in a high category (3.27) with different values of alms (3.49), infaq (3.23) and waqf (3.10). Therefore, it can be concluded that Ramadan contributes positively to the social solidarity of Muslim communities in Indonesia. The result can be used to develop a model of social solidarity in overcoming the problem of disintegration. Furthermore, it improves Muslim philanthropy for social welfare and to overcome the problem of poverty.Contribution: This article contributes to the sustainable development goal of poverty alleviation. It focuses on a multidisplinary religious perspective from textual and hermeneutical studies within the paradigm of Qur’an studies.